Orotracheal tube versus supraglottic devices in biological, chemical and radiological disasters: meta-analysis in manikin-based studies - Israel Baptista de Souza Borges; Magali Rezende de Carvalho; Marcel de Souza Quintana; Dalmo Valério Machado de Lima; Bruno Leal Barbosa; Alexandre Barbosa de Oliveira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To compare the mean time of orotracheal intubation and insertion of supraglottic airway devices, considering healthcare providers wearing waterproof overall, gloves, boots, eye protection and mask at the Chemical, Biological, Radiological and Nuclear context in simulation setting. Methods: Six databases were searched. The selected studies were put in a pool of results using a random-effects meta-analysis, with standardized mean differences and calculation of 95% confidence intervals. Results: Nine observational studies were included. Regarding reducing time to provide ventilatory support, subgroup analyses were made. The emergency setting subgroup: -12.97 [-16.11; -9.83]; I2 = 64%. The surgery setting subgroup: -14.96 [-18.65; -11.27]; I2 = 75%. Another analysis was made by reproductive methodology subgroups. Ophir's subgroup: -15.70 [-17.04; -14.37]; I2 = 0%. All meta-analyses had orotracheal tube as comparator. Conclusion: Moderate level of evidence was in favor of insertion of supraglottic devices because of fast application.